Biofilm Inhibition: The Role of Fixed Oil from Caryocar coriaceum in Fighting Resistant Bacterial Communities - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Saulo Almeida Menezes; Gabriel Gonçalves Alencar; Daiany Alves Ribeiro; Bárbara Fernandes Melo; João Pereira da Silva-Junior; Francisca de Fátima Silva de Sousa; Severino Denicio Gonçalves de Sousa; Marcos Aurélio Figueirêdo dos Santos; Dieferson Leandro de Souza; Luiz Neldecílio Alves Vitor; et al. (Bacteria)
Biofilms, formed by microbial communities that increase resistance to antibiotics, are responsible for chronic infections, making their combat a therapeutic priority. Taking this into account, the fruit Caryocar coriaceum stands out for its potential in the treatment of infectious diseases. The different parts of this plant can be used, and the fixed oil extracted from its fruit, rich in fatty acids, is indicated as responsible for its biological activities. Thus, the objective of this study was to evaluate the chemical composition of the fixed oil extracted from the fruits of C. coriaceum (FOCC), in addition to analyzing its action in the inhibition and pre-formed biofilm disruption of bacteria. The fixed oil was extracted from the internal mesocarp through exhaustive extraction with n-hexane, resulting in a yield of 38.29%. For antibiofilm evaluation, multidrug-resistant bacterial strains were exposed to the oil, and the antibiofilm activity was verified through biofilm formation and pre-formed biofilm disruption assays. The chemical analysis of the fixed oil of C. coriaceum (FOCC) identified eight fatty acids, representing 98.2% of the total composition, with a predominance of oleic acid (60.1%) and palmitic acid (33.5%). FOCC demonstrated approximately 70% inhibition of Streptococcus mutans biofilm formation at a concentration of 10 mg/mL and approximately 60% inhibition against Staphylococcus aureus and Pseudomonas aeruginosa. In pre-formed biofilm disruption, FOCC showed low efficacy against S. mutans and P. aeruginosa but showed greater activity against Enterococcus faecalis and S. aureus. These results indicate that FOCC has the potential to prevent biofilms, but its pre-formed biofilm disruption capacity is still limited.